Development of a Questionnaire to Measure Public Perceptions of the Role of Community Pharmacy in Public Health (PubPharmQ) - Delyth H. James; Rose Rapado; Sarah L. Brown; Joanne Kember; Karen L. Hodson; Amie-Louise Prior (MDPI AG, 2023)
Background: Community pharmacies are well placed to provide public-health interventions within primary care settings. This study aimed to establish the general public's perceptions of community pharmacy-based public-health services in the UK by designing a structured questionnaire to assess the barriers and facilitators to optimizing this role. Methods: A standardized questionnaire was developed informed by the literature, additional semi-structured interviews, and synthesis of key findings with the authors' previous research based on data generated from eight focus groups. The original 42-item questionnaire was distributed online from May to June 2021 via social media platforms to capture the views of non-regular pharmacy users. Following exploratory factor analysis, and Cronbach's alpha analysis, total Likert scale response scores were calculated. Results: Of the 306 responders, 76.8% were female with a mean age of 34.5 years (SD = 15.09). The most prevalent pharmacy use reported was 1-2 times a year (28.1%). Exploratory factor analysis revealed four scales: Expertise, Role in Public Health, Privacy, and Relationship (18 items) with acceptable internal consistency and good face and content validity. Awareness of well-established pharmacy services was high; however, responders demonstrated poor awareness of public-health-related services and low recognition of pharmacy expertise for this role. A lack of an established relationship with community pharmacies and privacy concerns were also perceived barriers. Conclusions: Based on these findings, considerable effort is needed to increase public awareness and address these concerns if strategic plans to utilize community pharmacy in the delivery of public-health policy are to be successful. The PubPharmQ provides a novel, structured questionnaire to measure the public's perceptions of community pharmacy's role in public health.